A MEASUREMENT OF THE MEAN LIFETIMES OF CHARGED AND NEUTRAL B-HADRONS - Abreu, P; Adam, W; Adye, T; Agasi, E; Ajinenko, I; Aleksan, R; Alekseev, G; Algeri, A; Allen, P; Almehed, S; Alvsvaag, S; Amaldi, U; et al. (1993)
The decays of B-hadrons have been reconstructed using the charged particles recorded in the DELPHI silicon microstrip detector. The sum of the charges of the secondaries determines the charge of the B-hadron parent. Some 232 114 multihadronic Z0 decays recorded during the 1991 run of LEP at centre-of-mass energies between 88.2 GeV and 94.2 GeV yield 253 B-hadron candidates with well-measured charge. From these the mean lifetimes of neutral and charged B-hadrons are found to be 1.44 ± 0.21 (stat.) ± 0.14(syst.) ps and 1.56 ± 0.19(stat.) ± 0.13(syst.) ps respectively. The ratio of their lifetimes is 1.09+0.28-0.23(stat.) ± 0.11 (syst.). Under some assumptions on the abundance and lifetime of the Λ0b and B0s states, the B0 and B+ lifetimes are inferred.